Variabilidade genética e a eficiência de seleção no caráter dormência de sementes em aveia-preta(Avena strigosa Schreb.) - Moliterno, Enrique Alfredo Parachu (2008)
Seed dormancy is a trait shown by a large variety of weedy plants, which helps the purpose of perpetuating the species through space and time by delaying germination until specific environmental cues happen. Black oat, a temperate forage grass, is widely used for pasture and as a cover crop in minimum tillage systems in Southern Brazil. However, the largest portion of the seed sown belongs to an old variety, which has no genetic identity, contributing to the appearance of undesirable agronomic traits in a crop species such as seed dormancy. This trait is hold responsible for turning black oat into a potential weedy species in areas sown to other cool season cereals, such as wheat and barley. Three methods were used to screen and select for black oat genotypes expressing low seed dormancy, i.e. screening of lines collected throughout different agricultural regions of the state of Rio Grande do Sul; subjecting a specific line of the species to the effects of two chemical and one physical mutagens and crossbreeding between selected lines and commercial cultivars of the species. All three methods were undertaken under a glasshouse environment (without temperature control), and since there are no known vegetative morphological traits associated to seed dormancy the procedure consisted on selecting seedlings from non dormant seeds. These were grown in the glasshouse environment and their progeny seeds tested for germinability, thus repeating the cycle. Genetic progress was slow for all three methods and cross breeding resulted the most difficult way for the creation of new genotypes, as only less than 8% of all pollinated flowers yielded hybrid seeds. Differences in germinability percentage among seeds of the first and second selection cycles were largest for the line- screening method, less for mutant seed phenotypes and minimum for the crossbreeding method, in which only F1 seeds were tested for germinability. On average, mutant seed treatments yielded 15% germinability after the first selection cycle, increasing to 20% germinability by the end of the second selection cycle. The screening of black oat lines yielded an initial 7% germinability, which increased to 36% germinability by the end of the second cycle. A common trend for all three methods was that seed germinability was highest during the first half of the standard germination test period for oat species, which implies that seedling selection was exercised for two traits simultaneously, i.e. absence of seed dormancy and seed vigor. The identification of several genotypes producing seeds expressing both traits increases the opportunity for genetic progress in this species.